The Role of Upper Body Biomechanics in Elite Racewalkers - Gravestock, Helen J.; Tucker, Catherine B.; Hanley, Brian (Frontiers in Sports and Active Living, 2021)
The aim of this study was to analyze the link between the upper and lower body during racewalking. Fifteen male and 16 female racewalkers were recorded in a laboratory as they racewalked at speeds equivalent to their 20-km personal records (men: 1:23:12 (± 2:45; women: 1:34:18 (± 5:15)); a single representative trial was chosen from each athlete for analysis and averaged data analyzed. Spatial variables (e.g., stride length) were normalized to stature and referred to as ratios. None of the peak upper body joint angles were associated with speed (p < 0.05) and there were no correlations between pelvic motion and speed, but a medium relationship was observed between peak pelvic external rotation (right pelvis rotated backwards) and stride length ratio (r = 0.37). Greater peak shoulder extension was associated with lower stride frequencies (r = −0.47) and longer swing times (r = 0.41), whereas peak elbow flexion had medium associations with flight time (r = −0.44). Latissimus dorsi was the most active muscle at toe-off during peak shoulder flexion; by contrast, pectoralis major increased in activity just before initial contact, concurrent with peak shoulder extension. Consistent but relatively low rectus abdominis and external oblique activation was present throughout the stride, but increased in preparation for initial contact during late swing. The movements of the pelvic girdle were important for optimizing spatiotemporal variables, showing that this exaggerated movement allows for greater stride lengths. Racewalkers should note however that a larger range of shoulder swing movements was found to be associated with lower stride frequency, and smaller elbow angles with increased flight time, which could be indicative of faster walking but can also lead to visible loss of contact. Coaches should remember that racewalking is an endurance event and development of resistance to fatigue might be more important than strength development.